Production Monitoring System Using Overall Equipment Effectiveness (OEE) Method to Improve Stamping Machine Performance - Gun Gun Maulana (Politeknik Negeri Lhokseumawe, 2022)
One of the factors that support success in the manufacturing industry is the smoothness of the production process. There are six factors that affect engine performance, known as the Six Big Loss. Six significant losses are the cause of production equipment not operating normally, namely: start-up loss, set up or adjustment loss, cycle time losses, speed loss, breakdown loss and defect loss. Downtime that often occurs results in decreased productivity, and production results do not reach the target. Production machine downtime is often not known by some parties, especially superiors positions such as managers, section heads and maintenance division. The goal to be achieved in this research is to design and realize a performance monitoring system for a stamping machine based on the internet of things (IOT) to increase the effectiveness of the machine with the optimal amount of production. The method used to determine machine performance is Overall Equipment Effectiveness (OEE). OEE is one of the methods available in TPM or Total Productive Maintenance. The study results show that machine downtime notifications are informed quickly using an alarm system.